Self-Regulated Learning Skills in Vocational Students Based on Their Self-Evaluation - Meidi Sirk (International Journal for Research in Vocational Education and Training)
Context: The importance of both self-regulated and self-directed learners has been emphasised in lifelong learning. However, in theory, self-regulated learning (SRL) serves as a basis for becoming a self-directed learner. Therefore, SRL (which includes certain skills) needs to be developed in vocational education and training alongside specialist training in order to meet the demands of the labour market, where employees should be capable of continuous learning. Previous studies based on the experiences of vocational teachers, and mainly focusing on adolescent students, have highlighted that many vocational students have low levels of SRL skills. However, there is a lack of research exploring student perspectives on their own SRL skills. It is unclear what factors influence their SRL and what support they need for developing SRL. The aim of this article is to analyse and describe the differences in the SRL skills of vocational students based on their self-evaluation and the factors related to their SRL.